Sistema de informações pluviométricas do estado do Rio de Janeiro: SIPRJ - Sucharov, Elza Correia; Picanço, Cibele Gonçalves; Marques, Valdo da Silva; Rodrigues, Marcos Aurélio Faial (Anuário do Instituto de Geociências, 1996)
The SIPRJ - Rainfall Information System for the State of Rio de Janeiro is a PC software developed to simplify and allow easy consulting of rainfall data and statistical information on monthly and yearly basis' for the period from 1940 to 1993 for the State of Rio de Janeiro. The SIPRJ program should be installed in a PC with a capability at least of 80286, a RAM memory of 640 kb, a HD with 15 MB free memory, a HD floppy drive and an operating system MS DOS 3.0 or later.